2019
DOI: 10.1177/1059712319844182
|View full text |Cite
|
Sign up to set email alerts
|

Robot’s adaptive emotional feedback sustains children’s social engagement and promotes their vocabulary learning: a long-term child–robot interaction study

Abstract: In this article, we present an emotion and memory model for a social robot. The model allowed the robot to create a memory account of a child’s emotional events over four individual sessions. The robot then adapted its behaviour based on the developed memory. The model was applied on the NAO robot to teach vocabulary to children while playing the popular game ‘Snakes and Ladders’. We conducted an exploratory evaluation of our model with 24 children at a primary school for 2 weeks to verify its impact on childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 72 publications
(110 reference statements)
3
63
0
Order By: Relevance
“…The results of Ahmad et al (2019) are consistent with findings from human studies and demonstrate that feedback does not only enhance children's language performance, but also engages children. Positive feedback engages because it validates children's answers and thus boosts their confidence (Henderlong and Lepper, 2002;Zentall and Morris, 2010).…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of Ahmad et al (2019) are consistent with findings from human studies and demonstrate that feedback does not only enhance children's language performance, but also engages children. Positive feedback engages because it validates children's answers and thus boosts their confidence (Henderlong and Lepper, 2002;Zentall and Morris, 2010).…”
Section: Introductionsupporting
confidence: 85%
“…Based on previous findings in literature regarding the role of feedback in second language learning, and previous studies that address feedback in child-robot interactions (Ahmad et al, 2019), we hypothesize that children will be more task-and robot-engaged when receiving (either preferred or dispreferred) feedback than when they do not receive feedback (H1a). Especially positive feedback is expected to increase the children's intrinsic motivation for the task and thus their engagement.…”
Section: This Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Possible explanations for the robot tutor's success include the robot's novelty. Anecdotally, children in the current study expressed great excitement about the robot tutor, and a recent review also emphasizes high enjoyment and anthropomorphic tendencies for robots in children in our age range (Ahmad et al, 2019;van Straten et al, 2020). A study similarly did not find an effect of tutor type, but showed that children gazed more at a robot tutor than a human tutor (Westlund et al, 2017).…”
Section: Social Robot and Human Tutors In L2 Vocabulary Teachingmentioning
confidence: 39%
“…Recent improvements in speech understanding and generation have prompted the increased utilization of language-based agents in realworld scenarios. Existing commercial agents like Siri 1 and Alexa 2 tend to be highly transactional, focusing on delivering the correct content in responses. However, as research identifies additional potential areas of deployment in service [41] and entertainment [18] roles, there is a need for agents to deliver responses that are not only correct, but emotionally appropriate.…”
Section: Introductionmentioning
confidence: 99%